The Role of Girls as Mothers in Harry Potter Series - Marcelina Fransisca; Jenny Mochtar (kata, 2017)
This study focuses on the role of the female characters in Harry Potter series. It aims to find out the ways the female characters, Hermione Granger, Ginny Weasley, and Luna Lovegood take a mother role for Harry, whereas they are in their teenage years. Using Barthes’ theory on myths, this study identifies that there are two myths that are in operation, the myth that girls are supposed to be mothers and the myth that mothers are supposed to protect, nurture, and educate. As the agents of the myths,the three teenage girls willingly take their role as  mothers  role that are assigned to them. These three female characters take their roles as mothers to Harry in how they protect, nurture, and educate Harry. In response to this, Harry also succumbs to the position of being protected, nurtured and educated by these three girls. Despite Rowling’s claims on her being a feminist when she said that “I’ve always considered myself as a feminist” (Rowling, 2011), she cannot escape the myths on girls and women. Rowling sees that  being a mother is the most powerful role for girls and women